PENGGUNAAN APLIKASI GOOGLE FORM SEBAGAI MEDIA EVALUASI PEMBELAJARAN AKIDAH AKHLAK KELAS IX DI MTS AL-I’ANAH KOSAMBI - Siti Hanifah; Iwan Hermawan; Kasja Eki Waluyo (Universitas Islam Madura, 2022)
There are many media that can be used for home learning for an educator, it becomes a solution for online learning. That is to use the learning media for an educator for the learning process. In the current situation, a teacher is led to be more creative in learning activities so that students remain passionate in learning activities even if they are carried out remotely. During the current pandemic, teachers still use learning evaluation techniques that tend to be monotonous and conventional, namely assignments through student worksheets that are then photographed sent through the teacher's WhatsApp platform. But it turns out that very few students who work on the evaluation of the learning given, so it has an impact on the empty grades of students. Therefore, the author wants to know the use of google form application as a medium of evaluation on the subjects of grade IX moral beliefs in MTs Al-I'anah Kosambi. The approach used in this study uses a qualitative approach because it shows a description of the phenomenon of the response of teachers and students to the use of Google Form as a medium of evaluation of the learning of Akhlak Religious subjects in MTs Al-I'anah Kosambi.